H.O.S. Cokroaminoto dan Transformasi Nasionalisme Islam pada Era Kolonial - Agus Mahfudin Setiawan; Jihan Nur Azizah; Uswatun Hasanah (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
The rise of Indonesian nationalism in the early 20th century is closely related to the role of Sarekat Islam (SI) which developed from an economic organization to a people's political movement. H.O.S. Tjokroaminoto's thinking integrates Islamic values with modern ideas such as social justice and zelfbestuur, arousing cross-class national consciousness. This study uses historical methods (heuristic, criticism, interpretation, historiography) to examine primary documents such as congress archives and Tjokro's speeches as well as scientific literature. Previous studies have rarely highlighted the SI's political strategy in building inclusive nationalism. This research shows that SI is able to transform people's economic awareness into political movements through political education, organizational consolidation, and regeneration. The results of the study affirmed SI as a milestone of national awakening that united the people against colonialism. This finding has implications for the importance of understanding the history of SI and Tjokroaminoto's thoughts as an inspiration to strengthen political education and nationalism based on social justice in today's Indonesia